“Death is not a lover”: An ecofeminist perspective on the “extinction” of women in Cormac McCarthy’s The Road - Chartudomdej, Sani (Humanities, Arts and Social Sciences Studies, 2022)
The Pulitzer Prize-winning novel The Road by Cormac McCarthy has been widely praised for raising concerns about ecological destruction and inciting conversations surrounding human extinction. Focusing on the aspect of gender, this research article essentially argues that the author uses post-apocalyptic elements together with the anti-heroic mode in an attempt to express a post-feminist point of view. The two components are, supposedly, meant to work together not only to challenge traditional gender ideologies but also to suggest that the book has transcended the essentialism and binary thinking of conventional feminism when it comes to gender roles and relations. However, when viewed from an ecofeminist perspective, a correlation between the author’s biased treatment of women and nature is revealed. While McCarthy expands the roles of his male characters, he under-represents, marginalizes and victimizes both women and nature in The Road. By advocating and perpetuating male domination of women and nature, the author negates women’s experiences and connections to the earth while sabotaging their contributions and abilities in protecting and preserving it. The “extinction” of women in the book essentially overlooks their role and significance in shaping and crafting a sustainable ecological narrative. This ends up undermining the novel’s reputation and status as a celebrated part of the environmental writing canon as it fails to resonate with a wider audience.